Liquid phase hydrogenation of α,β-unsaturated aldehydes over gold supported on iron oxides - Lenz, Jennifer (2009)
Goethite, hematite, and iron oxide supported on alumina are employed as supports for gold catalysts. Several samples are prepared and are characterized by TEM, TPR, and XANES. The catalysts are tested for the liquid phase hydrogenation of crotonaldehyde and cinnamaldehyde in a Batch reactor at 100 C and at 1 MPa of H2 employing isopropanol as the solvent. Gold particles supported on the different iron oxides are more selective than the ones supported on an inert oxide (c-Al2O3). Gold supported on hematite presents the highest selectivity toward the unsaturated alcohol. It is concluded that the promotional effect of iron on gold is neither due to the redox properties of the support nor due to the presence of charged gold particles. No dependence of selectivity to crotyl alcohol or to cinnamyl alcohol on gold particle size was observed. The origin of the improved selectivity to the unsaturated alcohol of Au/iron oxides would be related to morphological aspects of gold particles.2 employing isopropanol as the solvent. Gold particles supported on the different iron oxides are more selective than the ones supported on an inert oxide (c-Al2O3). Gold supported on hematite presents the highest selectivity toward the unsaturated alcohol. It is concluded that the promotional effect of iron on gold is neither due to the redox properties of the support nor due to the presence of charged gold particles. No dependence of selectivity to crotyl alcohol or to cinnamyl alcohol on gold particle size was observed. The origin of the improved selectivity to the unsaturated alcohol of Au/iron oxides would be related to morphological aspects of gold particles.